2018
DOI: 10.1177/0306624x18801653
|View full text |Cite
|
Sign up to set email alerts
|

The Tendency to Make Arrests in Domestic Violence: Perceptions From Police Officers in China

Abstract: The present study examines police officer attitudes and responses to domestic violence on a sample of 520 officers in a southern Chinese city. The police officers were asked to respond to two vignette scenarios depicting husbands assaulting their wives. The results show high correlations between officer responses to the two vignettes: Husbands are much more likely to be arrested than wives. The results of logistic regression analysis reveal that officers who view their profession as that of a law enforcer are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…Conversely, police officers were less likely to recommend mediation when they held traditional views of women in Chinese society. This finding may be related to the Confucian philosophy that emphasizes society should rely on hierarchy in human relations, group cohesiveness, and ethical governance (Zhao, Zhang, Zhao, & Wang, 2018). Namely, it is possible that within China, DV is perceived as an interpersonal conflict, and people should turn to morality or ethics for guidance—not the police.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Conversely, police officers were less likely to recommend mediation when they held traditional views of women in Chinese society. This finding may be related to the Confucian philosophy that emphasizes society should rely on hierarchy in human relations, group cohesiveness, and ethical governance (Zhao, Zhang, Zhao, & Wang, 2018). Namely, it is possible that within China, DV is perceived as an interpersonal conflict, and people should turn to morality or ethics for guidance—not the police.…”
Section: Discussionmentioning
confidence: 91%
“…The research site of the current study was a prefecture city located in Guangxi Zhuang Autonomous Region (equivalent to a province) in China (see R. Zhao, Zhang, Yong, & Yao, 2018). The city itself is composed of two core urban districts and two populous counties.…”
Section: Data Collection and Samplementioning
confidence: 99%
See 2 more Smart Citations
“…Their attitudes and responses on domestic violence cases, however, have rarely been studied in mainland China. By employing similar methods used in the existing literature (Saunders, 1995; Stith, 1990), Zhao et al’s (2018) study revealed that an officer’s likelihood of arresting male offenders was greater compared to arresting female victims. Specifically, officers who viewed their profession as a law enforcer were more likely to arrest either husbands or wives, officers who believed that domestic violence was a private issue were less inclined to arrest the husbands, and those who held profeminist attitudes were more inclined to arrest the husbands.…”
Section: The Contributions Of This Special Issuementioning
confidence: 99%